Dampak Media Sosial Dalam Praktik Jurnalistik (Study Kasus Jurnalis Tribun Sumsel) - Hidayat Riski Saputra; Sumaina Duku; Ahmad Harun Yahya (CV. ITTC INDONESIA, 2024)
The development of print media from time to time always experiences development, one of which is social media. The presence of new media in industry 4.0 and society 5.0 today, has changed the dynamics of life. With the presence of new media, everything that is far becomes close through the development of information and communication technology, which is complicated to be practical and changes everything that is manual to automatic. The presence of new media and convergence is a new dynamic for news media in Indonesia, because the existence of media convergence makes their reach wider and unlimited, less likely to be left behind by enthusiasts.The purpose of this study is to determine the impact of social media on journalistic practices. Researchers used descriptive qualitative methods. This type of descriptive qualitative method is used as a description of how the impact of social media in journalistic practices on South Sumatra Tribune journalists. The data collection techniques used in this research are observation, interviews, and documentation. The theory used in this research is Difussion Of Innovation Theory because by using this theory, researchers can understand the decision-making process in making news, including what factors influence news selection and how information is processed before reaching the audience. From the research that has been conducted, it is found that the impact of social media on journalistic practices is mostly